Planning and integrated administration of the coastal marine area of the Callao - Cabrera Carranza, Carlos (2005)
Many countries of Latin America have used the sectoral planning I united purpose to administer activities and coastal resources, but in most of the cases these programs have not reached the maturation. The antecedents of study socioeconòmicos and environmental that one has in the study area, added to environmental monitoreos, you interview and other mensuration instruments that are used, allow to face a design of Planning and Integrated Administration of the coastal area, based on a holistic perspective. The present work has as purpose to propose an a methodology that serves as base to assign the best uses from the territory to the productive activities and services in the port of the Callao, to minimize the environmental impacts originated by the growth of activities and for the population’s growth in the short and medium term. This allows to the National University bigger than San Marcos to complete their investigation list and projection to the community coherent proposals that you/they help in the improvement of the quality of the population’s life, the economic growth and the Classification and sustainable Handling of our territory settling down.